PENANAMAN NILAI-NILAI PENDIDIKAN ISLAMI MELALUI KEGIATAN RUTIN DI PONDOK PESANTREN UMMUL QURA AMUNTAI - Maskanah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Instilling Islamic educational values through routine activities in students is good because it can form an Islamic personality. Based on this statement, the focus of this study is the instillation of Islamic educational values through routine activities at the Ummul Qura Amuntai Islamic Boarding School and the purpose of this study is to determine the instillation of Islamic educational values through routine activities at the Ummul Qura Amuntai Islamic Boarding School. The type of research used in this study is field research using a qualitative descriptive approach. The data sources for this study are ustadz and ustadzah, as well as students, and data related to the problems discussed. Data collection techniques are carried out by means of observation, interviews, and documentation. The data processing uses data reduction, data display, and data verification. Furthermore, it is analyzed using a qualitative descriptive method. Based on the results of the study, it is known that the instillation of Islamic educational values through routine activities at the Ummul Qura Amuntai Islamic Boarding School carried out by students from Monday to Sunday, namely the five daily prayers in congregation, reading istighosah or special wirid, teaching and learning activities of book studies, tadarus Al-Qur'an, mudzakarah, mutala'ah, tahlilan, reading of maulid habsyi, reading burdah, ta'lim assemblies on Wednesday afternoons and evenings, gotong royong, and morning exercise. There are activities that are carried out regularly, especially in the instillation of Islamic educational values with the aim of forming Islamic habits of students. The instillation of Islamic educational values through routine activities at the Ummul Qura Amuntai Islamic Boarding School includes the values of aqidah, sharia values, and moral values as a form of forming Islamic habits and personalities of students based on the Al-Qur'an and As-Sunnah. So that with the instillation of Islamic educational values, especially through routine activities, it is hoped that students will be able to practice them and increase the potential of Islamic education and shape students into people who believe and are devoted to Allah SWT